Does heavy mental workload affect moral sensitivity among critical care unit nursing professionals? a cross-sectional study - Hosein Zahednezhad; Nasrin shokrollahi; Reza Ghanei Gheshlagh; Pouya Farokhnezhad Afshar (BMC, 2021)
Abstract Background Moral sensitivity creates the basic attitude in providing effective ethical care to patients. Heavy mental workload is a major concern of critical care nursing professionals, which could adversely affect nursing staff and patients. The present study aimed to investigate the effects of mental workload and some demographic variables on the moral sensitivity of critical care nursing professionals. Methods This cross-sectional, descriptive-correlational study was performed on 181 nursing professionals working in the critical care units of Shahid Rajaei Cardiovascular Medical and Research Center in Tehran, Iran. Data were collected using a demographic questionnaire, the moral sensitivity questionnaire, and the NASA-task load index to assess mental workload. Data analysis was performed in SPSS version 22 using descriptive statistics, independent t-test, Pearson's correlation-coefficient, and regression analysis. Results The results of regression analysis yielded no statistical significant relationship between heavy mental workload and moral sensitivity of the critical care nursing professionals, while clinical experience had a positive, significant association with moral sensitivity. Conclusions Although care nursing professionals experience a heavy mental workload in critical care units, it does not decrease their moral sensitivity. In addition, experienced nurses have higher moral sensitivity and lower mental workload. Therefore, it seems that nursing managers should pay special attention to the importance of employing experienced nurses along with younger nurses.